(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Pregnant women with KEK [Kekurangan Energi Kronis, Chronic Energy Deficiency] who are given purple sweet potatoes and green beans, to increase MUAC [Mid-Upper Arm Circumference] and BMI [Body Mass Index] due to KEK, as KEK towards the childbirth process can result in difficult and prolonged labor, imminent preterm birth (IPP), postpartum hemorrhage, as well as an increase in caesarean section procedures. Objective: To analyze the effects of providing purple sweet potatoes and green beans to pregnant women with CED in the Working Area of Muara Komam Community Health Center. Method: This research employs a quantitative research design, specifically a Pre-Experimental Design utilizing the One-Group Pretest-Posttest Design. In this study, the sampling method used is simple purposive sampling. Therefore, in this design, there is a pretest administered before the treatment is given. The sample consists of 30 respondents. Results: The average MUAC and BMI before the provision of purple sweet potatoes and green beans to pregnant women with CED were 22.73 with a standard deviation of 0.000. After the provision, the mean values were 19.45 with a standard deviation of 0.000. In the control group, the MUAC was 22.17 and the BMI was 18.89, with a standard deviation of 0.000 and a p-value of 0.036.